Lithological substrates influence tropical dry forest structure, diversity, and composition, but not its dynamics - Muñoz, Rodrigo; Enríquez, Moisés; Bongers, Frans; López-Mendoza, Rey David; Miguel-Talonia, César; Meave, Jorge A. (Frontiers in Forests and Global Change, 2023)
Introduction Tropical dry forests (TDF) are not only the most widespread tropical forest type but also the most threatened forest ecosystem worldwide. Yet, because their dynamics have been insufficiently studied, our knowledge about the factors responsible for the spatial and temporal variability in TDF dynamics remains very limited. In this study, we aimed (1) to assess the effects of two lithological substrates on TDF structure, diversity, and species composition, and (2) to determine whether and how these substrates affect temporal dynamics on TDF attributes. Methods We used information gathered through a 12-year long annual monitoring of 14 old-growth TDF permanent plots in southern Mexico, seven of which were established on limestone and seven on phyllite. Previous work shows that limestone-derived soils have higher humidity, conductivity, and phosphorous and calcium contents, but lower nitrogen content. Results TDF structure and diversity attributes were consistently higher on limestone TDF, while canopy height was higher on phyllite TDF. By contrast, temporal variation in TDF attributes, demographic rates (recruitment, growth, and mortality) and attribute residence times were indistinguishable between substrates. We also found a strong differentiation of species composition between substrates, yet substrates did not influence the temporal behavior of composition. Discussion Our results suggest that limestone is a more favorable environment for TDF development (soil-effects mechanism), but the flora of the forest on phyllite seems to be better adapted to cope with harsher environmental conditions (composition-effects mechanism), which counterbalances the environmental advantage of limestone, ultimately resulting in spatially homogeneous TDF dynamics at the landscape level. Future studies should examine the role of functional attributes on old-growth TDF dynamics, as this will allow a better understanding of the impacts of extreme climatic events on forest attributes and their dynamics, as well as to foresee potential ecosystem state shifts and tipping points.